PELUANG DAN TANTANGAN PEMASARAN USAHA TERIPANG DAERAH PESISIR KOTA BONTANG KALIMANTAN TIMUR - Ayu Dita Sar; Desy Meliana (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
Malahing Township, Bontang City has very potential in sea cucumber business. In marketing sea cucumbers are still manual by selling processed products to collectors. So the marketing margins are high because collectors buy from fishermen at cheap prices and resell at more prices. Research with qualitative methods to see the opportunities and challenges of sea cucumber marketing in fact. The results of respondents indicate that the level of education and public awareness of natural resources is still lacking. Abundant potential resources and the role of the company's CSR partners in assisting provide a prosperous opportunity. Empowerment needs to be done to the community on the importance of sea cucumber management and transportation capital that facilitates the marketing of sea cucumbers. Keywords: marketing, sea cucumbers, malahing township